The treatment of patients with medically unexplained physical symptoms in China: a study comparing expectations and treatment satisfaction in psychosomatic medicine, biomedicine, and Traditional Chinese Medicine - Fritzsche, Kurt; Xudong, Zhao; Anselm, Kathrin; Kern, Stephanie; Wirsching, Michael; Schäfert, Rainer (The international journal of psychiatry in medicine, 2011)
Objective: Little is known about treatment for patients with medically unexplained symptoms (MUS) in China. This study investigates the treatment expectations and treatment satisfaction of patients with MUS in psychosomatic medicine, biomedicine, and Traditional Chinese Medicine (TCM). Method: In a cross-sectional survey, n = 96 (10.3%) out of 931 participating patients were screened positive for multiple somatoform symptoms. These patients answered questionnaires concerning symptom duration, number of doctor visits, functional impairment, emotional distress, treatment expectations, treatment satisfaction, and empathy in the consultation. The physicians filled in a questionnaire about applied or recommended treatment. Results: Most of the patients from psychosomatic medicine wanted psychotherapy. In TCM, 55% of the patients had already received TCM treatment and most of them wanted to continue TCM treatment. Patients in biomedicine did not express clear expectations; most of them had had no previous treatment. A combination of treatment methods was most prevalent in biomedicine in comparison to psychosomatic medicine and TCM. The outcome from the patients' point of view was significantly better in TCM than in psychosomatic medicine and biomedicine. Psychosomatic medicine's strength was the empathetic physician-patient interaction. Conclusions: From a bio-psychosocial perspective, these results suggest that various treatment approaches with various emphases can be effective depending on the patient's complaints, his illness beliefs, and what the physician offers. The results will be verified in a larger multicenter longitudinal study.
Gesehen am 04.05.2023